Technologies of the chemical industry and the requirements for them - Tursunov Shovkat Talibovich; Rubidinov Shoxrux G‘ayratjon o‘g‘li; Anvarxoʻjayev Ramzullohxoʻja Buzrukxoʻja oʻgʻli (Zien Journals, 2023)
The qualitative parameters of the provision of services are evaluated on the basis of subjective parameters that depend on the consumer properties of passengers, and objective parameters that depend on existing service standards, as well as quantitative values based on retrospective data.
Keywords: income; tariff; analysis